AN EXPLORING THE FACTORS STRUCTURE OF HUMAN RESOURCE OF SUPPLY CHAIN MANAGEMENT BASED ENTREPRENEURSHIP IN ACEH, INDONESIA - Saputra, Jumadil; Idris, Amiruddin; Albra, Wahyuddin (International Journal of Supply Chain Management, 2019)
The entrepreneurial opportunities emerge when certain individuals have insights into the value of resources that others do not. The resources such as alertness of entrepreneurial, knowledge, and ability become their own right. This study is intended to explore the factors structure of human resource of supply chain management based entrepreneurship in Aceh, Indonesia. The questionnaires were sent to 175 managers in firm, and were received back for an 86% response rate from 175 managers. The first factor analyzed was structure of the human resources. The summated entrepreneurship scores for managers were correlated, and responses to the human resource and entrepreneurship items were made using multivariate analysis of variance. These results identify the factors of human resources that are very influential on entrepreneurship in cluster 1 are Entrepreneurial Ability and Entrepreneurial Innovation.